Rapid fabrication and packaging of AlGaN/GaN high-temperature ultraviolet photodetectors using direct wire bonding. (21st June 2016) - So, Hongyun; Senesky, Debbie G
Abstract: Cost-effective fabrication and rapid packaging of AlGaN/GaN ultraviolet (UV) photodetectors was demonstrated using direct wire bonding between aluminum wires and a GaN surface. The fabricated photodetectors showed stable dark current levels through the highly conductive 2D electron gas (2DEG), which was electrically connected to aluminum bonding wires. At room temperature, the current passing through the 2DEG rapidly increased upon exposure to UV light because of the generated electrons excited in the AlGaN/GaN layers. In addition, the devices showed consistent and reliable operation at high temperatures up to 100 °C with mechanically stable bonding wires (pull strength of 3–5.2 gram-force), supporting the use of direct wire bonding techniques to fabricate simple AlGaN/GaN sensors for UV detection within harsh environments, such as downhole and space exploration applications.